Effects of turmeric powder on dough quality and bread quality - Nguyen , Dang My Duyen; Le , Tan Hoang (Journal of Technical Education Science, 2018)
Turmeric (Curcuma longa L.) powder is a spice, food preservative, popular colorant in India, China and Southeast Asia. Turmeric powder was used to substitute 0.5%, 1%, 1.5% and 2% of wheat ﬂour for making turmeric bread. Turmeric wheat dough was analyzed for gluten quality and CO2 holding ability. Quality of turmeric bread was assessed through nutritional value, sensory quality and curcumin content. The quality of gluten, the CO2 holding ability of dough decreased with the addition of 1.5% and 2% of wheat ﬂour with turmeric powder. The volume of turmeric bread decreased with the increasing amount of turmeric powder added to the bread. Nutritional content of turmeric bread was not significantly different from control samples. Curcumin was found in turmeric bread. The content of curcumin increased with the addition of turmeric powder. 1% addition of wheat ﬂour with turmeric powder showed acceptable sensory scores which were comparable to bread.